Effect of electroacupuncture on cyclic adenosine monophosphate-protein kinase A-vanillic acid receptor subtype 1 of the transient receptor potential/PLK-protein kinase C-vanillic acid receptor subtype 1 of the transient receptor potential pathway based on RNA-seq analysis in prostate tissue in rats with chronic prostatitis/chronic pelvic pain syndrome - Wu, Xiao-Ling; Cheng, Kai; Xu, Chang; Chai, Ye-Mao; Yap, Tai-Heng; Yang, Zhi-Wen; Sun, Qian-Hui; Tan, Yan; Zhang, Jia-Ni; Chen, Wei; Qiu, Xing-Hua; Yang, Xing-Yue; et al. (Frontiers in Neuroscience, 2022)
Objective To investigate the analgesic mechanism of electroacupuncture (EA) in rats with chronic prostatitis/chronic pelvic pain syndrome (CP/CPPS). Methods Thirty male SD rats were randomly divided into sham group, model group and EA group, with ten rats in each group. The CP/CPPS model was prepared by injecting 50 μL of complete Freund’s adjuvant (CFA) into the ventral lobes of the prostate tissue, and the sham group was injected with the same dose of saline. After 14 days of modeling, EA was applied to Guanyuan (CV4), Zhongji (CV3), Sanyinjiao (SP6) and Huiyang (BL35) in the EA group. After four courses, H&E staining was performed to observe the prostate tissue morphology, transcriptome sequencing (RNA-Seq) was performed for each group, and the selected signaling pathways were verified by qRT-PCR. Results The RNA-Seq analysis results suggested that the analgesic effect of EA on CP/CPPS may be achieved by regulating prostate gene expression, which may be related to multiple biological processes and signaling pathways. qRT-PCR results showed that the vanillic acid receptor subtype 1 of the transient receptor potential (TRPV1), phospholipase C (PLC), protein kinase C (PKC), cyclic adenosine monophosphate (cAMP), and protein kinase A (PKA) were all upregulated in the model group compared to the sham group (p < 0.01). Compared with the model group, TRPV1, PLC, PKC, cAMP, and PKA were all downregulated in the EA group (p < 0.05, p < 0.01). Conclusion The analgesic mechanism of EA on CP/CPPS may be achieved through modulation of cAMP-PKA-TRPV1/PLC-PKC-TRPV1 signaling pathway.